RECREATIONAL-ENVIRONMENTAL ASSESSMENT OF WATER RESOURCES IN SHIRAK REGION OF RA (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
For successful development of tourism industry in RA it is necessary to study and evaluate the tourist-recreational potential of the whole territory of the Republic as well as its regions. The bases for recreational use of the territory are first of all natural factors as they are not only tourist-recreational resources, but also they are prerequisites for recreational development.
Keywords: tourism; water tourism; recreation and environmental; assessment